MULTIMODAL COMMUNICATION ANALYSIS: THE HIGHER-LEVEL ACTIONS OF WAITERS AND WAITRESSES AT THREE RESTAURANTS IN TABANAN - Nugraha, Rama Urif Sukma; Myartawan, I Putu Ngurah Wage; Agustini, Dewa Ayu Eka (Universitas Pendidikan Ganesha, 2020)
This study aimed to analyze the multimodal communication of waiters and waitresses at three restaurants in Tabanan, Bali Province, in applying higher-level actions in serving foreign guests and investigating the functions of the higher-level actions of waiters and waitresses in serving the foreign guests. This study used theories proposed by Fishman (1972) cited in Suandi & Indriani (2016) on functions of using verbal and nonverbal communication, Krees and Van Leewuen 2006) on multimodal communication, and Norris (2004) on higher-level actions. The subjects of this study were four waiters and two waitresses who were working at three different restaurants in Tabanan regency. The results of this study showed that in each conversation, there were many sequences of higher-level actions used by waiters or waitresses to serve the foreign guests. The waiters and waitresses used a sequence of modes alternately or simultaneously in their higher-level actions, depending on the situation. The functions of waiters or waitresses’ higher-level actions in serving foreign guests made their messages clearer to foreign guests, and this made the waiters or waitresses’ messages more believable to the foreign guests.